The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/2050313x211046720
|View full text |Cite
|
Sign up to set email alerts
|

Bullous choroidal detachment requiring drainage following endoscopic cyclophotocoagulation

Abstract: Endoscopic cyclophotocoagulation is a relatively safe cyclodestructive procedure with a lower complication rate compared to trans-scleral cyclophotocoagulation. Serous choroidal detachment is a complication that has been reported following endoscopic cyclophotocoagulation; however, it is usually mild and transient. A case of bullous choroidal detachment with a flat anterior chamber requiring drainage after endoscopic cyclophotocoagulation is presented, along with a discussion on the risk factors precipitating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Cyclodestructive interventions such as endoscopic cyclophotocoagulation (ECP) and transscleral cyclophotocoagulation (TSCPC; including continuous wave and micropulse transscleral cyclophotocoagulation) have historically demonstrated lower rates of postoperative choroidal effusion development compared with trabeculectomy and GDDs, ranging from 0.36 to 5.7% [16,32] and 0 to 4% [16,33,34], respectively. Following ECP, postoperative choroidal effusions have been reported infrequently and have generally been mild and transient, resolving without the need for surgery.…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclodestructive interventions such as endoscopic cyclophotocoagulation (ECP) and transscleral cyclophotocoagulation (TSCPC; including continuous wave and micropulse transscleral cyclophotocoagulation) have historically demonstrated lower rates of postoperative choroidal effusion development compared with trabeculectomy and GDDs, ranging from 0.36 to 5.7% [16,32] and 0 to 4% [16,33,34], respectively. Following ECP, postoperative choroidal effusions have been reported infrequently and have generally been mild and transient, resolving without the need for surgery.…”
Section: Key Pointsmentioning
confidence: 99%
“…Following ECP, postoperative choroidal effusions have been reported infrequently and have generally been mild and transient, resolving without the need for surgery. However, Al Owaifeer et al [32] recently reported a case of large, bullous post-ECP choroidal effusions requiring surgical drainage.…”
Section: Risk Factors For Choroidal Effusion Developmentmentioning
confidence: 99%